2017
DOI: 10.1016/j.celrep.2017.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cingulate Cortex Modulation of the Ventral Tegmental Area in an Effort Task

Abstract: Information gained during goal pursuit motivates adaptive behavior. The anterior cingulate cortex (ACC) supports adaptive behavior, but how ACC signals are translated into motivational signals remains unclear. Rats with implants in the ACC and ventral tegmental area (VTA), a dopaminergic brain area implicated in motivation, were trained to run laps around a rectangular track for a fixed reward, where each lap varied in physical effort (a 30-cm climbable barrier). Partial directed coherence analysis of local fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 61 publications
6
50
1
Order By: Relevance
“…This model is also characterized by VTA hyperactivity, and normalizing VTA hyperconnectivity reduces the depressive, anhedonic phenotype (38). Another recent preclinical study has demonstrated that VTA connectivity with ACC mediates motivation for rewards (39) and heightened subgenual ACC connectivity has been previously demonstrated in patients with MDD (40). The current translational study confirms the observation of VTA hyperconnectivity in humans with depression who are free of medication.…”
Section: Discussionsupporting
confidence: 83%
“…This model is also characterized by VTA hyperactivity, and normalizing VTA hyperconnectivity reduces the depressive, anhedonic phenotype (38). Another recent preclinical study has demonstrated that VTA connectivity with ACC mediates motivation for rewards (39) and heightened subgenual ACC connectivity has been previously demonstrated in patients with MDD (40). The current translational study confirms the observation of VTA hyperconnectivity in humans with depression who are free of medication.…”
Section: Discussionsupporting
confidence: 83%
“…The ACC and VTA power spectrum density (PSD) functions from 1 to 30 Hz obtained from this dataset ( Figure 3) were consistent with prior reports showing that the VTA and ACC exhibited local peaks centered at $4 Hz (Elston and Bilkey, 2017;Fujisawa and Buzsá ki, 2011;Parker et al, 2014). For comparison, we also computed the PSDs and coherence of the nine rats roaming in a familiar open field.…”
Section: Decision Patterns Running Speeds and Latenciessupporting
confidence: 85%
“…We also observed an 8-to 12-Hz oscillation in the VTA, which was sustained throughout the trials (see Figure 4). However, because activity within and between the ACC and VTA has been previously reported to occur at $4 Hz (Elston and Bilkey, 2017;Fujisawa and Buzsá ki, 2011;Gao et al, 2007;Parker et al, 2014;Parker et al, 2015), the 8-to 12-Hz frequency band did not significantly differ between the open field and task conditions. To retain focus in the current paper, we focused our subsequent analyses on 2to 5-Hz activity (referred to as 4 Hz throughout the rest of this paper).…”
Section: Decision Patterns Running Speeds and Latenciesmentioning
confidence: 69%
See 1 more Smart Citation
“…In voles, the ACC has been implicated in regulating empathy-based consoling behavior towards the partner (Burkett et al, 2016). The VTA is a region known to modulate motivational, reward, and emotionally salient stimuli (Elston & Bilkey, 2017; Gunaydin et al, 2014). There is evidence that the VTA modulates DA release in prefrontal regions to regulate behaviorally relevant stimuli (Takahata & Moghaddam, 2002), including sexually relevant stimuli (Cortes et al, 2019).…”
Section: Discussionmentioning
confidence: 99%